肺動脈性肺高血圧症におけるクロライドチャネルClC3の病態生理学的役割の解明 - 天野, 泰樹; 山村, 彩; 藤原, 萌園; 近藤, るびい; 鈴木, 良明; 山村, 寿男 (日本薬理学会年会要旨集, 2023)
Pulmonary arterial hypertension (PAH) causes chronical increase in pulmonary artery pressure rises due to pulmonary vasoconstriction and vascular remodeling. Although several PAH drugs have been recently developed, no curative treatment has yet been achieved. Sustained elevation of cytosolic Ca2+ concentration ([Ca2+]cyt) is closely associated to PAH pathogenesis such as enhanced contraction and excessive proliferation of pulmonary artery smooth muscle cells (PASMCs). [Ca2+]cyt is regulated by membrane potentials which are partly regulated by voltage-dependent Cl- channels. In the present study, the functional expression of voltage-dependent Cl- channels (ClC family) was examined using PASMCs from normal subjects and idiopathic PAH (IPAH) patients. Expression analysis showed that ClC3 channel expression was increased in IPAH-PASMCs compared to normal-PASMCs. Swelling-activated Cl- channel currents were larger in IPAH-PASMCs than in normal-PASMCs, which were attenuated by ClC3 siRNA. The growth of IPAH-PASMCs was inhibited by Cl- channel blockers, niflumic acid and DIDS. ClC3 siRNA also decreased the proliferation of IPAH-PASMCs. In conclusion, the expression of ClC3 channels was upregulated in IPAH-PASMCs, resulting in excessive cell proliferation, which contributes to the pathogenesis of PAH.